Using galactitol dehydrogenase coupled with water-forming NADH oxidase for efficient enzymatic synthesis of L-tagatose - Su, Wen-Bin; Li, Fei-Long; Li, Xue-Yong; Fan, Xiao-Man; Liu, Rui-Jiang; Zhang, Ye-Wang (New biotechnology, 2021)
[Display omitted] •A novel bi-enzymatic strategy was developed for production of l-tagatose.•Water-forming NADH oxidase was first employed to recycle the NAD+ in l-tagatose production.•L-tagatose was effectively produced without by-products.•The highest yield (90.2 %) and productivity (7.61 mM h−1) were obtained. L-Tagatose, a promising building block in the production of many value-added chemicals, is generally produced by chemical routes with a low yield, which may not meet the increasing demands. Synthesis of l-tagatose by enzymatic oxidation of d-galactitol has not been applied on an industrial scale because of the high cofactor costs and the lack of efficient cofactor regeneration methods. In this work, an efficient and environmentally friendly enzymatic method containing a galactitol dehydrogenase for d-galactitol oxidation and a water-forming NADH oxidase for regeneration of NAD+ was first designed and used for l-tagatose production. Supplied with only 3 mM NAD+, subsequent reaction optimization facilitated the efficient transformation of 100 mM of d-galactitol into l-tagatose with a yield of 90.2 % after 12 h (obtained productivity: 7.61 mM.h−1). Compared with the current chemical and biocatalytic methods, the strategy developed avoids by-product formation and achieves the highest yield of l-tagatose with low costs. It is expected to become a cleaner and more promising route for industrial biosynthesis of l-tagatose.